Wage–Productivity Relationship in Indian Manufacturing Industries: Evidences from State-level Panel Data. (August 2019) - Jain, Hansa
Indian manufacturing industries have experienced the major effects of economic reforms. Since the effect of any policy is ultimately transferred to workers, this article is an attempt to determine the extent to which labour productivity and wages are inter-related in manufacturing industries. The study uses state-level panel data of manufacturing industries and empirically tests the relevance of marginal productivity theory of wages and efficiency wage theory. After confirming the stationarity of the series, various empirical tests such as cointegration, vector error correction mechanism and Granger causality are applied to check the long-run equilibrium relationship between wage growth and productivity growth. The study finds a divergence between wages and productivity in India as well as in the states. The empirical analysis confirms the existence of long-run relationship between the two variables and finds efficiency wage theory to be more appropriate as its long-term disequilibrium correcting process is quicker as compared to the marginal productivity theory. The study suggests for having a skill intensity matching with capital intensity. Appropriate level of skill and training among the workers will, on the one hand, increase their bargaining strength for more compensation, and on the other hand, will encourage them to produce more. JEL: J31, J24, O30, F66, L66